Synthesis of cationic polyacrylamide and its application in enhancing sludge dewatering

CN120518820BActive Publication Date: 2026-10-16SNF CHINA FLOCCULANT
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510661730.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-05-22
Publication Date
2026-10-16
Estimated Expiration
2045-05-22

AI Technical Summary

Technical Problem

[0004]本发明旨在解决现有技术中污泥脱水效率低的问题,‌通过联合使用氧化剂、阳离子聚丙烯酰胺和载体对污泥中EPS降解、絮凝,实现脱水效率的显著提升‌

Benefits of technology

[0007]本发明与现有技术相比,有如下益处:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120518820B_ABST
    Figure CN120518820B_ABST
Patent Text Reader

Abstract

The application discloses synthesis of cationic polyacrylamide and application of the cationic polyacrylamide in enhancing sludge dewatering, and cationic polyacrylamide is synthesized through a copolymerization method. Firstly, persulfate is added into sludge, the strong oxidizability of the persulfate breaks the restraint of extracellular polymeric substance (EPS) on water in the sludge, then cationic polyacrylamide flocculation is added, finally, a carrier is added to assist sedimentation, and sludge dewatering efficiency can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of sludge dewatering, specifically to the synthesis of cationic polyacrylamide and its application in enhancing sludge dewatering. Background Technology

[0002] With the acceleration of urbanization and industrial development, the volume of wastewater treated is constantly increasing, and so is the production of sludge. Sludge contains a large amount of water, organic matter, and other harmful substances. If not effectively treated and disposed of, it will cause serious environmental pollution. Therefore, sludge dewatering is a crucial step in the wastewater treatment process. Currently, commonly used sludge dewatering methods include natural drying, mechanical dewatering, and thermal drying. Among these, mechanical dewatering is one of the most frequently used methods. Its principle is to use mechanical force to squeeze out the water from the sludge, thereby reducing its moisture content. However, traditional mechanical dewatering methods have some problems, such as low dewatering efficiency, still high moisture content in the dewatered sludge, and a tendency to cause secondary pollution.

[0003] Extracellular polymeric substances (EPS) are high-molecular-weight metabolites secreted by microorganisms and exist on the cell surface. They account for approximately 60% to 80% of the total solids mass of sludge. EPS has a multilayered structure, and the distribution of protein content within EPS significantly affects the water content of the sludge. Furthermore, negatively charged EPS also affects the settling and filtration performance of sludge. Therefore, using oxidants and cationic polyacrylamide to degrade and flocculate EPS in sludge, followed by the addition of a carrier to assist settling, can effectively improve sludge dewatering efficiency. Summary of the Invention

[0004] This invention aims to solve the problem of low sludge dewatering efficiency in existing technologies. By combining an oxidant, cationic polyacrylamide, and a carrier to degrade and flocculate EPS in sludge, a significant improvement in dewatering efficiency is achieved. This invention provides a method for synthesizing cationic polyacrylamide, characterized by the following steps: Mix 850-900 parts of pure water, 340-390 parts of acrylamide, and 50-120 parts of cationic monomer by weight until homogeneous, then freeze to -2 °C. After purging with nitrogen for 20 min, add 0.03-0.05 parts of diethylenetriaminepentaacetic acid pentasodium, 0.3-0.5 parts of azobisisobutyronitrile, and 0.09-0.1 parts of sodium hypophosphite in sequence. Continue purging with nitrogen for 7 min, then add 0.002-0.006 parts of sodium persulfate. After 0.5 min, add 0.002-0.006 parts of sodium metabisulfite. Stop purging with nitrogen at the beginning of the reaction. After the reaction is completed, keep warm for 1 h, remove the gel block, granulate, dry, and grind to prepare cationic polyacrylamide flocculant.

[0005] The cationic monomer is one or two of allyltrimethylammonium chloride, benzylvinyltrimethylammonium chloride, (3-acrylamidopropyl)trimethylammonium chloride, N,N,N-trimethyl-3-(2-methylallylamido)-1-propanium chloride, methacryloyloxyethyl dimethylbenzylammonium chloride, and acryloyloxyethyl trimethylammonium chloride.

[0006] An application of cationic polyacrylamide to enhance sludge dewatering is characterized by the following steps: 1000 mL of sludge collected from a wastewater treatment plant is placed in a beaker and stirred at 400 r / min. Then, 5-5.5 g of potassium peroxymonosulfate is added to the beaker. After 30 min, the stirring speed is adjusted to 200 r / min, and 50-75 mL of an aqueous solution of 1 g / L cationic polyacrylamide flocculant is added. After stirring for 2 min, 3-4 g of silica sand is added, and stirring is continued for 3 min. Then, the stirring speed is reduced to 50 r / min, and stirring is continued for 15 min. Finally, the mixture is allowed to stand for 30 min. Then, the specific resistance (SFR), capillary water absorption time (CST), filter cake moisture content (WC), and content of different EPS components of the treated sludge are measured.

[0007] Compared with the prior art, the present invention has the following advantages: (1) Compared with electrocatalytic oxidation, photocatalytic oxidation and Fenton oxidation, the potassium persulfate oxidation method alone is simple to operate, has low equipment requirements and low cost. The subsequent flocculation and carrier-assisted sedimentation processes effectively improve the dewatering efficiency.

[0008] (2) The oxidation capacity of potassium persulfate breaks the binding of EPS to water, and then the flocculation of cationic polyacrylamide and carrier-assisted sedimentation effectively increase the sludge dewatering efficiency.

[0009] (3) The oxidation capacity of potassium persulfate alone is used to retain a certain degree of hydrophobicity of organic matter in sludge, which is conducive to forming hydrophobic association with moderately hydrophobic cationic groups on polyacrylamide and thus achieving more effective flocculation. Attached Figure Description

[0010] Figure 1 Raw sludge and treated SFR and CST; Figure 2 Moisture content of raw sludge and treated sludge; Figure 3 The content of different EPS components in raw sludge and treated sludge. Detailed Implementation

[0011] The following examples show sludge collected from a wastewater treatment plant: Sludge SRF: 19.8 × 10⁻⁶ 12m / kg, sludge CST: 98 s, sludge moisture content: 96.8%.

[0012] Example 1: A method for synthesizing cationic polyacrylamide and its application in enhancing sludge dewatering includes the following steps: 1. Mix 850 parts of pure water, 350 parts of acrylamide, 52 parts of allyltrimethylammonium chloride, and 55 parts of benzylvinyltrimethylammonium chloride by weight until homogeneous, then freeze to -2 °C. After purging with nitrogen for 20 min, add 0.04 parts of diethylenetriaminepentaacetic acid pentasodium, 0.5 parts of azobisisobutyronitrile, and 0.09 parts of sodium hypophosphite sequentially. Continue purging with nitrogen for 7 min, then add 0.003 parts of sodium persulfate. After 0.5 min, add 0.003 parts of sodium metabisulfite. Stop purging with nitrogen at the beginning of the reaction. After the reaction is complete, keep warm for 1 h, remove the gel block, granulate, dry, and grind to prepare cationic polyacrylamide flocculant. The structural formula is shown in the figure below: .

[0013] 2. Take 1000 mL of sludge collected from the wastewater treatment plant and place it in a beaker. Stir at 400 r / min. Then add 5.2 g of potassium peroxymonosulfate to the beaker. After 30 min, adjust the speed to 200 r / min and add 55 mL of 1 g / L cationic polyacrylamide flocculant aqueous solution from step 1. Stir for 2 min, then add 3.2 g of silica sand and continue stirring for 3 min. Then reduce the speed to 50 r / min and continue stirring for 15 min. Finally, let it stand for 30 min. Then measure the sludge specific resistance (SFR), sludge capillary water absorption time (CST), filter cake moisture content (WC), and the content of different EPS components.

[0014] Example 2: A method for synthesizing cationic polyacrylamide and its application in enhancing sludge dewatering includes the following steps: 1. Mix 860 parts of pure water, 355 parts of acrylamide, and 100 parts of benzylvinyltrimethylammonium chloride by weight until homogeneous, then freeze to -2 °C. After purging with nitrogen for 20 min, add 0.047 parts of diethylenetriaminepentaacetic acid pentasodium, 0.48 parts of azobisisobutyronitrile, and 0.092 parts of sodium hypophosphite sequentially. Continue purging with nitrogen for 7 min, then add 0.0035 parts of sodium persulfate. After 0.5 min, add 0.0032 parts of sodium metabisulfite. Stop purging with nitrogen at the start of the reaction. After the reaction is complete, keep warm for 1 h, remove the gel block, granulate, dry, and grind to prepare cationic polyacrylamide flocculant. The structural formula is shown in the figure below: .

[0015] 2. Take 1000 mL of sludge collected from the wastewater treatment plant and place it in a beaker. Stir at 400 r / min. Then add 5.3 g of potassium peroxymonosulfate to the beaker. After 30 min, adjust the speed to 200 r / min and add 58 mL of 1 g / L cationic polyacrylamide flocculant aqueous solution from step 1. Stir for 2 min, then add 3 g of silica sand and continue stirring for 3 min. Then reduce the speed to 50 r / min and continue stirring for 15 min. Finally, let it stand for 30 min. Then measure the specific resistance (SFR), capillary water absorption time (CST), filter cake moisture content (WC), and the content of different EPS components of the treated sludge.

[0016] Example 3: A method for synthesizing cationic polyacrylamide and its application in enhancing sludge dewatering includes the following steps: 1. Mix 865 parts of pure water, 360 parts of acrylamide, and 110 parts of (3-acrylamidopropyl)trimethylammonium chloride by weight until homogeneous, freeze to -2 °C, and purge with nitrogen for 20 min. Then, add 0.033 parts of diethylenetriaminepentaacetic acid pentasodium, 0.44 parts of azobisisobutyronitrile, and 0.093 parts of sodium hypophosphite sequentially. Continue purging with nitrogen for 7 min, then add 0.0031 parts of sodium persulfate. After 0.5 min, add 0.0035 parts of sodium metabisulfite. Stop purging with nitrogen at the beginning of the reaction. After the reaction is complete, keep warm for 1 h, remove the gel block, granulate, dry, and grind to prepare cationic polyacrylamide flocculant. The structural formula is shown in the figure below: .

[0017] 2. Take 1000 mL of sludge collected from the wastewater treatment plant and place it in a beaker. Stir at 400 r / min. Then add 5.1 g of potassium peroxymonosulfate to the beaker. After 30 min, adjust the speed to 200 r / min and add 55 mL of 1 g / L cationic polyacrylamide flocculant aqueous solution from step 1. Stir for 2 min, then add 3.1 g of silica sand and continue stirring for 3 min. Then reduce the speed to 50 r / min and continue stirring for 15 min. Finally, let it stand for 30 min. Then measure the specific resistance (SFR), capillary water absorption time (CST), filter cake moisture content (WC), and the content of different EPS components of the treated sludge.

[0018] Example 4: A method for synthesizing cationic polyacrylamide and its application in enhancing sludge dewatering includes the following steps: 1. Mix 872 parts by weight of pure water, 358 parts by weight of acrylamide, 53 parts by weight of allyltrimethylammonium chloride, and 56 parts by weight of acryloyloxyethyltrimethylammonium chloride. Freeze the mixture to -2 °C. After purging with nitrogen for 20 min, add 0.035 parts by weight of diethylenetriaminepentaacetic acid pentasodium, 0.5 parts by weight of azobisisobutyronitrile, and 0.095 parts by weight of sodium hypophosphite. Continue purging with nitrogen for 7 min. Then add 0.0033 parts by weight of sodium persulfate. After 0.5 min, add 0.004 parts by weight of sodium metabisulfite. Stop purging with nitrogen at the beginning of the reaction. After the reaction is complete, keep the mixture at this temperature for 1 h. Remove the gel block, granulate, dry, and grind it to prepare a cationic polyacrylamide flocculant. The structural formula is shown in the figure below. .

[0019] 2. Take 1000 mL of sludge collected from a wastewater treatment plant and place it in a beaker. Stir at 400 r / min. Then add 5.25 g of potassium peroxymonosulfate to the beaker. After 30 min, adjust the speed to 200 r / min and add 60 mL of 1 g / L cationic polyacrylamide flocculant aqueous solution from step 1. Stir for 2 min, then add 3.6 g of silica sand and continue stirring for 3 min. Then reduce the speed to 50 r / min and continue stirring for 15 min. Finally, let it stand for 30 min. Then measure the specific resistance (SFR), capillary water absorption time (CST), filter cake moisture content (WC), and the content of different EPS components of the treated sludge.

[0020] Example 5: A method for synthesizing cationic polyacrylamide and its application in enhancing sludge dewatering includes the following steps: 1. Mix 877 parts of pure water, 363 parts of acrylamide, and 108 parts of acryloyloxyethyltrimethylammonium chloride by weight until homogeneous, then freeze to -2 °C. After purging with nitrogen for 20 min, add 0.033 parts of diethylenetriaminepentaacetic acid pentasodium, 0.485 parts of azobisisobutyronitrile, and 0.097 parts of sodium hypophosphite sequentially. Continue purging with nitrogen for 7 min, then add 0.0033 parts of sodium persulfate. After 0.5 min, add 0.0036 parts of sodium metabisulfite. Stop purging with nitrogen at the start of the reaction. After the reaction is complete, keep warm for 1 h, remove the gel block, granulate, dry, and grind to prepare cationic polyacrylamide flocculant. The structural formula is shown in the figure below: .

[0021] 2. Take 1000 mL of sludge collected from a wastewater treatment plant and place it in a beaker. Stir at 400 r / min. Then add 5.29 g of potassium peroxymonosulfate to the beaker. After 30 min, adjust the speed to 200 r / min and add 61 mL of 1 g / L cationic polyacrylamide flocculant aqueous solution from step 1. Stir for 2 min, then add 3.5 g of silica sand and continue stirring for 3 min. Then reduce the speed to 50 r / min and continue stirring for 15 min. Finally, let it stand for 30 min. Then measure the specific resistance (SFR), capillary water absorption time (CST), filter cake moisture content (WC), and the content of different EPS components of the treated sludge.

[0022] Example 6: A method for synthesizing cationic polyacrylamide and its application in enhancing sludge dewatering includes the following steps: 1. By weight, 877 parts of pure water, 361 parts of acrylamide, 57 parts of methacryloyloxyethyl dimethyl benzyl ammonium chloride, and 51 parts of benzylvinyltrimethyl ammonium chloride were mixed evenly and frozen to -2 °C. After purging with nitrogen for 20 min, 0.038 parts of diethylenetriaminepentaacetic acid pentasodium, 0.46 parts of azobisisobutyronitrile, and 0.091 parts of sodium hypophosphite were added sequentially. After purging with nitrogen for another 7 min, 0.0031 parts of sodium persulfate were added. After 0.5 min, 0.0032 parts of sodium metabisulfite were added. Nitrogen purging was stopped at the beginning of the reaction. After the reaction was completed and kept at this temperature for 1 h, the gel block was removed, granulated, dried, and ground to prepare a cationic polyacrylamide flocculant. The structural formula is shown in the figure below: .

[0023] 2. Take 1000 mL of sludge collected from the wastewater treatment plant and place it in a beaker. Stir at 400 r / min. Then add 5.32 g of potassium peroxymonosulfate to the beaker. After 30 min, adjust the speed to 200 r / min and add 57 mL of 1 g / L cationic polyacrylamide flocculant aqueous solution from step 1. Stir for 2 min, then add 3.1 g of silica sand and continue stirring for 3 min. Then reduce the speed to 50 r / min and continue stirring for 15 min. Finally, let it stand for 30 min. Then measure the specific resistance (SFR), capillary water absorption time (CST), filter cake moisture content (WC), and the content of different EPS components of the treated sludge.

[0024] Comparative Example 1: Take 1000 mL of sludge collected from a wastewater treatment plant and place it in a beaker. Stir at 400 r / min. Then add 5.23 g of potassium peroxymonosulfate to the beaker. After 30 min, adjust the speed to 200 r / min and add 62 mL of 1 g / L commercial nonionic polyacrylamide aqueous solution. Stir for 2 min and then add 3.5 g of silica sand. Continue stirring for 3 min. Then reduce the speed to 50 r / min and continue stirring for 15 min. Finally, let it stand for 30 min. Then measure the specific resistance (SFR), capillary water absorption time (CST), filter cake moisture content (WC), and the content of different EPS components of the treated sludge.

[0025] The commercially available nonionic polyacrylamide used in this comparative example was purchased from Gongyi Xinqi Polymer Co., Ltd.

[0026] Comparative Example 2: 1. Mix 875 parts of pure water, 364 parts of acrylamide, 100 parts of acrylic acid, and 51 parts of sodium hydroxide by weight until homogeneous, freeze to -2 °C, and purge with nitrogen for 20 min. Then add 0.038 parts of diethylenetriaminepentaacetic acid pentasodium, 0.49 parts of azobisisobutyronitrile, and 0.092 parts of sodium hypophosphite in sequence. Continue purging with nitrogen for 7 min, then add 0.0034 parts of sodium persulfate. After 0.5 min, add 0.0036 parts of sodium metabisulfite. Stop purging with nitrogen at the beginning of the reaction. After the reaction is completed, keep warm for 1 h, remove the gel block, granulate, dry, and grind to prepare anionic polyacrylamide flocculant. 2. Take 1000 mL of sludge collected from a wastewater treatment plant and place it in a beaker. Stir at 400 r / min. Then add 5.35 g of potassium peroxymonosulfate to the beaker. After 30 min, adjust the speed to 200 r / min and add 57 mL of 1 g / L anionic polyacrylamide aqueous solution. Stir for 2 min, then add 3.15 g of silica sand and continue stirring for 3 min. Then reduce the speed to 50 r / min and continue stirring for 15 min. Finally, let it stand for 30 min. Then measure the sludge specific resistance (SFR), sludge capillary water absorption time (CST), sludge moisture content (WC), and the content of different EPS components after treatment.

[0027] Comparative Example 3: 1. Take 1000 mL of sludge collected from a wastewater treatment plant and place it in a beaker. Stir at 400 r / min. Then add 5.35 g of potassium peroxymonosulfate to the beaker. After 30 min, adjust the speed to 200 r / min and add 57 mL of 1 g / L commercial cationic polyacrylamide aqueous solution. Stir for 2 min, then add 3.15 g of silica sand and continue stirring for 3 min. Then reduce the speed to 50 r / min and continue stirring for 15 min. Finally, let it stand for 30 min. Then measure the sludge specific resistance (SFR), sludge capillary water absorption time (CST), sludge moisture content (WC), and the content of different EPS components after treatment.

[0028] In this embodiment, the commercial cationic polyacrylamide was purchased from Langfang Longke Energy Saving Technology Co., Ltd.

[0029] Comparative Example 4: 1. Take 1000 mL of sludge collected from a wastewater treatment plant and place it in a beaker. Stir at 400 r / min. Then add 5.35 g of potassium peroxymonosulfate to the beaker. After 30 min, adjust the speed to 200 r / min and add 50 mL of 2 g / L alum aqueous solution. Stir for 2 min and then add 3.15 g of silica sand. Continue stirring for 3 min. Then reduce the speed to 50 r / min and continue stirring for 15 min. Finally, let it stand for 30 min. Then measure the sludge specific resistance (SFR), sludge capillary water absorption time (CST), sludge moisture content (WC), and the content of different EPS components.

[0030] Sludge SFR and CST results are as follows Figure 1 As shown, sludge specific resistance reflects the filtration capacity of sludge. Generally speaking, the higher the sludge specific resistance, the worse the filtration performance. The sludge CST value can more accurately measure the sludge dewatering performance. The lower the CST value, the more free water in the sludge and the better the dewatering performance. In Examples 1-6, the SRF and CST of the sludge were significantly lower than those of the original sludge, indicating a significant improvement in dewatering efficiency. This is because after oxidation breaks the binding of EPS to water in the sludge, cationic polyacrylamide flocculates the sludge through netting, sweeping, and charge neutralization. Furthermore, the moderately hydrophobic cationic groups in the polyacrylamide form hydrophobic associations with the hydrophobic organic matter in the sludge, further enhancing the binding of polyacrylamide and pollutants. Finally, the addition of a carrier to assist sedimentation effectively improves the sludge dewatering effect. In contrast, Comparative Examples 1-2 used nonionic and anionic polyacrylamide, respectively, which had no charge neutralization effect on the sludge. The commercial polyacrylamide in Comparative Example 3 had a low degree of hydrophobicity of its cationic monomer and could not form hydrophobic associations with the organic matter in the sludge. In Comparative Example 4, alum could only bind to pollutants through charge neutralization. Therefore, the sludge dewatering efficiency was lower than that of the Examples.

[0031] Moisture content of raw sludge and treated sludge as follows Figure 2 As shown, after oxidation with an oxidant, flocculation with cationic polyacrylamide, and carrier-assisted sedimentation in Examples 1-6, the water content in the sludge filter cake was about 74%-75%, which significantly improved the sludge dewatering performance. In contrast, the water content in the sludge filter cake of Comparative Examples 1-4 was about 81%-86%, which was lower than the dewatering performance of the Examples.

[0032] Content of different EPS components in sludge, such as Figure 3 As shown, EPS can be classified into soluble EPS (S-EPS), loosely bound EPS (LB-EPS), and tightly bound EPS (TB-EPS). In Examples 1-6, the EPS, after oxidation, is converted into smaller dissolved organic matter, and the pollutant surface carries a negative charge, thus being flocculated by cationic polyacrylamide. Therefore, the EPS in Examples 1-6 is significantly reduced. In contrast, the nonionic and anionic polyacrylamides in Comparative Examples 1-2 have poor flocculation effects on the oxidized dissolved organic matter. The commercial cationic polyacrylamide in Comparative Example 3 has low hydrophobicity and cannot bind to organic matter in the sludge through hydrophobic association. The alum in Comparative Example 4 can only bind to pollutants through charge neutralization, therefore the final EPS content is higher than in the Examples.

Claims

1. An application of cationic polyacrylamide to enhance sludge dewatering, characterized in that: Take 1000 mL of sludge collected from a wastewater treatment plant and place it in a beaker. Stir at 400 r / min. Then add 5-5.5 g of potassium peroxymonosulfate to the beaker. After 30 min, adjust the speed to 200 r / min and add 50-75 mL of 1 g / L cationic polyacrylamide flocculant aqueous solution. Stir for 2 min, then add 3-4 g of silica sand and continue stirring for 3 min. Then reduce the speed to 50 r / min and continue stirring for 15 min. Finally, let it stand for 30 min. Then measure the specific resistance (SFR), capillary water absorption time (CST), filter cake moisture content (WC), and content of different EPS components of the treated sludge. The synthesis method of cationic polyacrylamide flocculant includes the following steps: 850-900 parts of pure water, 340-390 parts of acrylamide, and 50-120 parts of cationic monomer are mixed evenly by mass and then frozen to -2 ℃. After purging with nitrogen for 20 min, 0.03-0.05 parts of diethylenetriaminepentaacetic acid pentasodium, 0.3-0.5 parts of azobisisobutyronitrile, and 0.09-0.1 parts of sodium hypophosphite are added sequentially. After purging with nitrogen for 7 min, 0.002-0.006 parts of sodium persulfate are added. After 0.5 min, 0.002-0.006 parts of sodium metabisulfite are added. Nitrogen purging is stopped at the beginning of the reaction. After the reaction is completed and kept at the temperature for 1 h, the gel block is removed, granulated, dried, and ground to prepare cationic polyacrylamide flocculant. The cationic monomer is one or two of allyltrimethylammonium chloride, benzylvinyltrimethylammonium chloride, (3-acrylamidopropyl)trimethylammonium chloride, N,N,N-trimethyl-3-(2-methylallylamido)-1-propanium chloride, methacryloyloxyethyl dimethylbenzylammonium chloride, and acryloyloxyethyl trimethylammonium chloride.

Citation Information

Patent Citations

  • Method for synthesizing sludge dewatering agent of positive ions

    CN101050050A